Cover Feature: In‐Fjord Substitution in Expanded Helicenes: Effects of the Insert on the Inversion Barrier and Helical Pitch (Chem. Eur. J. 53/2021). Issue 53 (21st August 2021) - Suárez‐Pantiga, Samuel; Redero, Pablo; Aniban, Xaiza; Simon, Martin; Golz, Christopher; Mata, Ricardo A.; Alcarazo, Manuel
Abstract : Like the arms of a dancer, which are waved following the rhythm of the music but avoid colliding with her head or her body; the flexible arms of expanded helicenes find different pathways to reverse their position depending on the size and nature of the insert placed in the innermost zone of their fjord. This work presents the synthesis of a series of in‐fjord substituted expanded helicenes and an estimation of their inversion barriers through state‐of‐the‐art quantum calculations. Interestingly, the energetic profile of the inversions is intensively affected by the interplay of steric and attractive London dispersion interactions. More information can be found in the Full Paper by R. A. Mata, M. Alcarazo, et al. (DOI: 10.1002/chem.202102585 ).